2022
DOI: 10.1002/dc.24965
|View full text |Cite
|
Sign up to set email alerts
|

Cellular fibroadenoma versus phyllodes tumors: A pre‐operative diagnostic approach based on radiological and cytological features

Abstract: Objective This study has been designed in an effort to identify the clinico‐radiological and cytological features that could effectively help in differentiating cellular fibroadenoma (CFA) and phyllodes tumors (PT), which have several overlapping characteristics. Method Histologically proven cases of CFA and PT were reviewed. Cytological features were assessed and categorized. Clinical and radiological details were also evaluated and he the two groups were compared statistically. Results A total of 43 FA and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This may explain the improved performance after including age in the ResNet model. Tumor size is one of the key factors that must be considered in the differential diagnosis of PTs and FAs [10,20,32,33]. In accordance with previous studies, we found that PTs are usually larger than FAs in tumor size.…”
Section: Discussionsupporting
confidence: 91%
“…This may explain the improved performance after including age in the ResNet model. Tumor size is one of the key factors that must be considered in the differential diagnosis of PTs and FAs [10,20,32,33]. In accordance with previous studies, we found that PTs are usually larger than FAs in tumor size.…”
Section: Discussionsupporting
confidence: 91%
“…Much of the debate involving phyllodes tumors is focused on preoperative diagnosis, probability of recurrence, and adjuvant therapy after surgical excision has been performed depending on the classification of the tumor. Due to the numerous histological similarities between phyllodes tumors and cellular fibroadenomas which both display increased stromal cellularity, it can be difficult to distinguish between the two through fine needle aspiration or core needle biopsy alone [ 5 , 7 ]. The ability to distinguish between these two tumors preoperatively can not only aid in the intraoperative planning for determining proper excisional margins and management of the axilla but can also help to prevent overtreatment or undertreatment of the patient [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the numerous histological similarities between phyllodes tumors and cellular fibroadenomas which both display increased stromal cellularity, it can be difficult to distinguish between the two through fine needle aspiration or core needle biopsy alone [ 5 , 7 ]. The ability to distinguish between these two tumors preoperatively can not only aid in the intraoperative planning for determining proper excisional margins and management of the axilla but can also help to prevent overtreatment or undertreatment of the patient [ 4 , 5 ]. Wide surgical margins of at least 1 cm were originally thought to be optimal for local control [ 3 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations